Bioacumulação de metais em estruturas gonadais do caranguejo-uçá, Ucides cordatus (Linnaeus, 1763) (Ocypodidae), em manguezais da costa paraense - SILVA, Messias Reis da (2022)
The degree of contamination of coastal ecosystems by metals can put all associated biota at risk. Thus, by analyzing the concentration of Cd, Cu, Cr, Pb and Mn in the gonads of male and female of the mangrove crabs (Ucides cordatus), the present study aimed to determine the degree of contamination by these metals in the different gonadal stages of this species in the mangroves of Vila do Bacuriteua, on the coast of Pará. Metal concentrations were measured by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Of the 57 crabs analyzed, males (n=30) were larger and heavier than females (n=27) and for the four identified gonadal stages, most males were in the "developing" stage (DE), while females in the “rudimentary” (RU) stage, with no male and female individuals being found in the “immature” (IM) and “advanced” (AV) stages. The analysis of the concentration of Cd, Cu, Cr, Pb and Mn revealed that the empty stage (ES, Esgotado em Português) presented the highest concentrations for Cd, Cu and Mn, while in the ED stage they were for Cr and Pb, although the concentrations of Cd and Pb had been largely recorded below the detection limit. These elements were only detected in the RU and ES stages and in a few samples. Females showed concentration values a little higher than males, although no significant difference was recorded between the analyzed metals. The results presented here revealed a process of bioaccumulation of these metals in the gonadal structures of U. cordatus. Finally, even considering the study area a well-preserved maguezal area, the results obtained here also revealed that the gonads of both sexes of the uçá crab have high concentrations of Cr and Pb, above the limits allowed by the regulatory agency in the country.